2020
DOI: 10.1111/tmi.13504
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities and the COVID‐19 pandemic dynamics in Africa

Abstract: The debate around the COVID‐19 response in Africa has mostly focused on effects and implications of public health measures, in light of the socio‐economic peculiarities of the continent. However, there has been limited exploration of the impact of differences in epidemiology of key comorbidities, and related healthcare factors, on the course and parameters of the pandemic. We summarise what is known about (a) the pathophysiological processes underlying the interaction of coinfections and comorbidities in shapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 114 publications
2
55
0
Order By: Relevance
“…Deaths which occurred after laboratory samples tested positive were not reported back to our Centre. A large number of deaths from COVID-19 pandemic have occurred in the United States, China, the United Kingdom, Italy, Iran and Spain, with relatively fewer deaths recorded in Africa [ 35 ]. The relatively lower death toll of COVID-19 in Africa may be due to differences in genetic or climatic factors, or perhaps the impact is yet to be felt [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deaths which occurred after laboratory samples tested positive were not reported back to our Centre. A large number of deaths from COVID-19 pandemic have occurred in the United States, China, the United Kingdom, Italy, Iran and Spain, with relatively fewer deaths recorded in Africa [ 35 ]. The relatively lower death toll of COVID-19 in Africa may be due to differences in genetic or climatic factors, or perhaps the impact is yet to be felt [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of deaths from COVID-19 pandemic have occurred in the United States, China, the United Kingdom, Italy, Iran and Spain, with relatively fewer deaths recorded in Africa [ 35 ]. The relatively lower death toll of COVID-19 in Africa may be due to differences in genetic or climatic factors, or perhaps the impact is yet to be felt [ 35 ]. Studies have shown that comorbidities have the tendency of increasing individual’s susceptibility to COVID-19, especially among the elderly [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the low intensity and lethality of the national epidemics in most African countries suggest hypothetical protective interactions of the high burden of tuberculosis (and/or BCG coverage) and tropical parasitic diseases, along with the lack of health-care infrastructure capable of clinically detecting and confirming COVID-19 cases, the implementation of social distancing and hygiene, international air traffic flows, the climate, the relatively young and rural population, the genetic polymorphism of the angiotensin-converting enzyme 2 receptor, cross-immunity and the use of antimalarial drugs [ [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] ]. However, the detection of a new variant of the SARS-CoV-2 in South Africa (variant 501Y·V2) in middle December 2020 with preliminary studies suggesting that the variant is associated with a higher viral load, which may suggest potential for increased transmissibility, might challenge the low transmissibility, low lethality trend observed so far in most African Countries [ 81 ].…”
Section: Evidence Of the Syndemic Nature Of The Sars-cov-2 Pandemicmentioning
confidence: 99%
“…There is a real threat of vaccine-preventable disease outbreaks because of COVID-19 related disruptions to routine immunisation (IRC, 2021 Children are unlikely to be the first recipients of COVID-19 vaccine, as they generally are in malaria immunisation programmes (Blair in Sisay et al, 2020: 7). Children aged five years and younger are the most vulnerable age group affected by malaria, although this age group has been relatively spared from COVID-19 mortality and severe morbidity so far (Anjorin et al, 2020). Multiple immunisation programmes running concurrently with COVID-19 vaccination will have long-term benefits.…”
Section: Continue Child Vaccination Programmesmentioning
confidence: 99%